Diversity and ethnobotanical uses of wild food plants in Girimanik Natural Forest, Central Java, Indonesia - Bunga Melati; Santhyami Santhyami (Lambung Mangkurat University-Indonesia, 2026)
Wild plant as one of Non Timber Forest Product (NTFP) have significant potential as an alternative food source for communities, especially in areas that still have access to natural resources. This research aims to (1) inventory the types of wild plants utilized as food by the community and analyze their usage forms, and (2) determine the community consensus value and the priority of wild food plant species considered important based on the analysis of the Informant Consensus Factor (ICF) and Relative Frequency of Citation (RFC) indices. The research was conducted using participatory observation methods, semi-structured interviews with key informants and general informants, as well as field exploration (guided tour) to discover and collect plant samples. Data were analyzed descriptively and quantitatively using the ICF and RFC indices. The research results show the presence of various species of wild food plants utilized by the community, with a dominance of herbaceous plants. The family with highest diversity of species is Asteraceae. The leaves are the most commonly utilized component, primarily employed as vegetables. The species Galinsoga parviflora has the highest RFC value (RFC=0.81) and is used as a vegetable, although the snack food category possesses the highest ICF value (ICF=1.00), followed by staple food (ICF=0.86). This research shows that wild plants play an important role in supporting food security based on local biological resources and emphasizes the importance of documenting and preserving traditional community knowledge related to the utilization of wild plants.